Hubungan Amerika Serikat dan Meksiko Menghadapi Money Laundering Tahun 2008-2012 - Ridho, Ardo; Kresnawati, Megahnanda Alidyan (Global and Policy Journal of International Relations, 2022)
Transnational crimes involving the United States and Mexico, especially money laundering, have had various impacts on both countries and have been a serious problem for many years. The United States and Mexico are cooperating in dealing with this problem, the aim is to as soon as possible overcome or resolve the problem of this transnational crime. This study uses qualitative research methods using the concept of transnational crime and international cooperation. Through this research, the author will analyze the relationship and cooperation between the United States and Mexico in tackling the problems of Money Laundering that occurred in the two countries.DOI: https://doi.org/10.33005/jgp.v10i01.3567